Efficiency and Cost Analysis of Cell Saver Auto Transfusion System in Total Knee Arthroplasty - Mustafa Gökhan Bilgili; Ersin Erçin; Cemal Kural; Altuğ Duramaz; Cevdet Avkan; Gökhan Peker; Serdar Hakan Başaran (Balkan Medical Journal, 2014)
Background: Blood loss and replacement is still a controversial issue in major orthopaedic surgery. Allogenic blood transfusion may cause legal problems and concerns regarding the transmission of transfusion-related diseases. Cellsaver Systems (CSS) were developed as an alternative to allogenic transfusion but CSS transfusion may cause coagulation, infection and haemodynamic instability.